Granular cell tumor of esophagus removed with endoscopic submucosal dissection - Sadettin HÜLAGÜ; Ömer ŞENTÜRK; Cem AYGÜN; Yeşim GÜRBÜZ; Orhan KOCAMAN; Altay ÇELEBİ and Buğra Tolga KONDUK (Turkish Journal of Gastroenterology, 2019)
-